UPAYA AMERIKA SERIKAT DALAM MENGATASI KASUS PELANGGARAN HAM OLEH KELOMPOK LORD’S RESISTANCE ARMY DI UGANDA - Sari, Mutia Novela; Sukandar, Rudi (Universitas Hasanuddin, 2019)
Crimes against humanity in the form of human rights violations in Uganda was caused by internal conflict which was triggered by Lord's Resistance Army (LRA). The conflict started in 1987 and lasted over 20 years. Not only in Uganda, LRA also attacked three neighboring countries, such as Republic Democratic Congo, South Sudan, and Central Africa. During the conflict, LRA caused more than 100,000 deaths, abducted more than 60,000 children, and displaced more than 2.5 million civilians. Due to the prolonged internal conflict, the Ugandan government was considered to fail to protect its citizens thus the international community intervened to overcome this problem, as conducted by the United States. This paper attempted to reveal the U.S. efforts to overcome cases of human rights violations by LRA group in Uganda and the impact of such efforts to the protection of civilians. The research reveals the case of human rights violations in Uganda can be overcome after efforts had been carried out by the U.S. and supported with development and economy recovery for areas and social and healthy recovery for citizens of Uganda.